IVUS-guided versus OCT-guided PCI among patients presenting with acute coronary syndrome - Mostafa Abdelmonaem; Abdelrahman Abushouk; Ahmed Reda; Sherif Arafa; Hisham Aboul- Enein; Ahmed Bendary (The Egyptian Heart Journal, 2023)
Abstract Background Intravascular imaging modalities such as intravascular ultrasound (IVUS) and, more recently, optical coherence tomography (OCT) improved the visualization of coronary anatomy and plaque pathology. We aimed to compare the procedural and short-term outcomes between IVUS-guided and OCT-guided percutaneous coronary interventions (PCIs) in patients with acute coronary syndrome (ACS). Methods In the present retrospective study, we reviewed the data of 50 patients who had IVUS-guided PCI and 50 patients who had OCT-guided PCI for ACS between January 2020 and June 2021. Intravascular imaging was done before and after stenting. Both groups were compared in terms of minimal luminal area (MLA), stent dimensions, final minimal stent area (MSA) and stent expansion as well as negative angiographic outcomes. Patients were followed for six months to record major adverse cardiac events (MACE). Results The patients’ mean age was 57 ± 13 years with male predominance (78%). The radiation time and dose were significantly higher among IVUS group. Pre-stenting MLA was significantly higher in IVUS group (2.63 mm vs. 2.22 mm in OCT, P = 0.013). Stent expansion was significantly higher among OCT group (97% vs. 93% in IVUS group, P = 0.001) with no significant difference between both groups regarding MSA [mm2] (8.88 ± 2.87 in IVUS vs. 8.1 ± 2.76 in OCT, P = 0.169). No significant difference between both groups was noted regarding contrast volume, edge dissection, tissue prolapse, and no reflow. The rates of six-month MACE were significantly higher in the IVUS group. Conclusions OCT-guided PCI in ACS is safe and is associated with similar MSA to that of IVUS-guided PCI. Future randomized trials are needed to confirm these findings. Graphical Abstract